Main tendencies of temporal changes for concentration of priority pollutants in sediments of the coastal areas at Vladivostok (Peter the Great Bay, Japan Sea) - A. V. Moshchenko; T. A. Belan; T. S. Lishavskaya; A. V. Sevastianov; B. M. Borisov (Известия ТИНРО)
Concentrations of hydrocarbons, phenols, DDT and its metabolites, Cu, Pb, Fe, Ni, DDD/DDE and DDD+DDE/DDT ratios, and total level of chemical contamination (TPF index) in the bottom sediments are traced for 16 stations in the coastal areas at Vladivostok in 1982−2017. Temporal variations of the concentrations and derived indices are classified to 4 types of dynamics, using the methods of exploratory and confirmatory factor analysis, crosscorrelation analysis, and fuzzy set classification procedure. They are: primary contamination; secondary contamination; exponential growth; and polymodal dynamics. These variations are induced by two main sources of pollution, such as the industrial influx including wastes from Vladivostok and nearby settlements, aeolian transfer and polluted precipitations, and the terrigenous influx with polluted freshwater discharge. Impact of the first source prevails in the Golden Horn Bay, Diomid Inlet and Eastern Bosphorus Strait, and the second source is important for the Amur and Ussuri Bays (the coast of Vladivostok in these bays is influenced by both sources with predominance of the second). The terrigenous impact has two modes depended on certain processes of contamination: the permanent pollution inherent in the types of secondary contamination and exponential growth and the extreme pollution that forms the polymodal dynamics. The secondary contamination follows the primary one with a lag of 6–7 years. The secondary contamination of terrigenous usually has inverse correlation with the Razdolnaya/Suifen River discharge; for instance, strengthening of the freshwater inflow causes lower concentrations of Cu and Pb in the bottom sediments due to dilution effect. On the contrary, contamination depends directly on the Razdolnaya/Suifen River discharge for the exponential growth of terrigenous — the stronger the freshwater inflow, the higher the concentrations of Fe, Ni, and phenols (the latter is a sign of eutrophication). The types of dynamics change following the balance between pollution and self-cleaning of the sediments that is determined by external factors, as a drop in economic activity and its subsequent recovery, limitation and finally ban for using of tetraethyl lead additive, extreme floods on rivers, etc.